A work on Samuya Foods Manufacturing, Inc. - Diaz, Irma; Estrada, Eric D.C.; Ladim, Jose Angelo A. (Diliman, Quezon City College of Engineering, 1999)
The Samuya Food Manufacturing, Inc. is a 100 percent Filipino Corporation. It is a company engaged in the manufacture and sales of various food products such as peanut butter, coco jam, confectionary products, and other minor ones. This study is focused on the processing of peanut butter since it is the "flagship" product of the company. Peanut butter is the main contributor to its income. The manufacturing involves processes such as roasting, peeling, sorting, mixing, grinding and finishing or packing. After conducting an analysis of the company's present system and condition, the major problems identified are the following : inefficient materials storage and handling and, no standard method in the sorting operation. The other minor problems determined from the streamline analysis include : no safety and precautionary measures; one hour late logging in of the the sealing workers, frequent machine breakdowns, idle raw materials due to the grinding process, and product "vulnerable" to foreign particles. Due to time constraints, the work study is limited to the investigation of 340-gram bottle production. All the data regarding the production of peanut butter are gathered through plant visits and interviews with the key personnel. The company background, its systems and procedures, plant layout, and general working conditions are documented in this study. The problems of the existing production system are determined by cause and effect relationships using the STREAMLINE analysis, then the major problems are isolated. After the identification of the problem, alternatives are formulated and evaluated using the COST-BENEFIT analysis. The alternative with the highest cost benefit ratio is discussed further. The study group offered recommendations which focused on the improvement of the flow of inventory or stocks, determination of the optimal work schedule for the workers in the sealing task, improvement of the sorting method, and of the working conditions. The study yielded the following results : there is a bottleneck in the packing/sealing section due to the one-hour late scheduling for the workers in the sealing process. There is no clear indication of the basis for the inventory flow. Two methods are adopted in the sorting process- the use of "bilao" and use of the conveyor. There is inefficiency in the materials handling especially from the peeling to the sorting section, which requires the most number of transportation. There are no standard methods for crucial processes like SORTING, MIXING, GRINDING and PACKING/SEALING. There is insufficient NATURAL VENTILATION especially in the roasting section, which generates the heat in the plant. The assembly line in the packing/sealing section is balanced so the bottleneck is caused by the difference in the log-in times of the workers. Among the alternatives presented, the following are chosen: To reduce the accumulation of filled-bottles in the sealing section all workers in the said section are now required to log in at 6:00 am with an 8 minute period to prepare their tools, clothing, etc. The alternative suggesting the painting of walls to have a clear indication of the length of storage of raw materials is chosen. Recommendations on improving the working conditions such as installation of exhaust fans to provide natural ventilation, posting of warning signs, installation of a rough surfaced flooring in the grinding section, etc. For the company to employ a preventive maintenance scheme, the study group designed a Machine Repair Form that will record the nature of the breakdowns and which machines incurred the breakdown. A Tally Sheet is designed to be able to record the occurence of machine breakdowns and establish a maintenance schedule. The Engineering Department keeps a mater copy of the designed Machine Repair Form and a duplicate copy is provided to the Production Department.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Samuya Food Manufacturing Inc; Butter trade; Systems analysis